The Fundamental Kantian Aporia - Moya Bedoya, Juan Diego (2025)
My paper regards a Kantian dilemma: either we omit the claim that (p) there are things in itself, because we must omit every assertion without epistemic justification, or we omit the claim, essential from the point of view of the Kantian theory of categories, that (q) categories only have cognitive significance if they inform phenomena (at least one phenomenon). P places Immanuel Kant outside from ontological realism; q places Kant, outside from empiricism. But Kantian epistemology is a realistic empiricism. Therefore, this dilemma poses Immanuel Kant out of Kantianism, that is, it compels Kant to give up Kantian epistemology.